Juramentación Rector Rodrigo Arias Camacho. (UNED, 1999)
Discurso de Rodrigo Arias Camacho. Aparecen en la mesa principal Guillermo Vargas Salazar, Constantino Bolaños Herrera, Celedonio Ramírez Ramírez